2021
DOI: 10.3390/w13020242
|View full text |Cite
|
Sign up to set email alerts
|

Soil Water Dynamics Under Different Land Uses in Loess Hilly Region in China by Stable Isotopic Tracing

Abstract: Exploring soil water dynamics under different land use types is important for water resource management and vegetation restoration in the Loess Plateau. In this study, we investigated the hydrogen and oxygen isotopic compositions of soil water from four different land use types to explore the mechanism of soil water movement and transformation and analyse the influence of land use. The results show that the range of stable isotopes (δD and δ18O) in soil water was smaller than that in precipitation. Values for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…This was more consistent with the findings of many scholars. For example, the studies, by Du et al (2021) in the Loess Plateau and Pu et al (2020) in the Hani terraces, had shown that isotope variation of soil water was significant in shallow soil layers on the semi-sunny aspect and more stable in deeper soil layers (Yong et al 2020). It has also been shown that shallow soil water of 0-30 cm was the main water source of subalpine shrubs and exhibits greater variability affected by precipitation, evaporation and transpiration (Szutu and Papuga 2019;.…”
Section: Differences In Stable Isotopes Of Soil Watermentioning
confidence: 99%
See 1 more Smart Citation
“…This was more consistent with the findings of many scholars. For example, the studies, by Du et al (2021) in the Loess Plateau and Pu et al (2020) in the Hani terraces, had shown that isotope variation of soil water was significant in shallow soil layers on the semi-sunny aspect and more stable in deeper soil layers (Yong et al 2020). It has also been shown that shallow soil water of 0-30 cm was the main water source of subalpine shrubs and exhibits greater variability affected by precipitation, evaporation and transpiration (Szutu and Papuga 2019;.…”
Section: Differences In Stable Isotopes Of Soil Watermentioning
confidence: 99%
“…Since surface soil water is significantly affected by precipitation, evaporation and plant transpiration, isotope values of soil water gradually decrease with increasing of soil depth. With the increase of soil depth, the mixing of surface soil water and deep soil water caused the isotope values of soil water increasing and gradually stabilizing Du et al 2021;Zhao et al 2018).…”
Section: Differences In Stable Isotopes Of Soil Watermentioning
confidence: 99%
“…This was more consistent with the ndings of many scholars. For example, the studies, by Du et al (2021) in the Loess Plateau and Pu et al (2020) in the Hani terraces, had shown that isotope variation of soil water was signi cant in shallow soil layers on the semi-sunny aspect and more stable in deeper soil layers (Yong et al 2020). It has also been shown that shallow soil water of 0-30 cm was the main water source of subalpine shrubs and exhibits greater variability affected by precipitation, evaporation and transpiration (Szutu and Papuga 2019; .…”
Section: Differences In Stable Isotopes Of Soil Watermentioning
confidence: 99%
“…Since surface soil water is signi cantly affected by precipitation, evaporation and plant transpiration, isotope values of soil water gradually decrease with increasing of soil depth. With the increase of soil depth, the mixing of surface soil water and deep soil water caused the isotope values of soil water increasing and gradually stabilizing Du et al 2021;Zhao et al 2018). There were differences in the uctuation of δ 18 O values of soil water of different aspects at different soil depths.…”
Section: Differences In Stable Isotopes Of Soil Watermentioning
confidence: 99%
“…Studies have suggested that soil water storage capacity in vegetated land is substantially higher than in bare or fallow land [19][20][21]. In addition, the spatiotemporal distribution and migration of soil water under different land cover types have been extensively studied [22][23][24][25][26][27][28]. Yang et al [29] reported that different intensities of desiccation occurred below 3-m soil depths in various forestlands, excluding young apple orchards and shrub stands (Hippophae rhamnoides and Caragana korshinskii); soil desiccation intensity increased with an increase in the age of forest trees.…”
Section: Introductionmentioning
confidence: 99%